A Phase IIa, Randomized, Double-Blind Study of Remimazolam (CNS 7056) Versus Midazolam for Sedation in Upper Gastrointestinal Endoscopy. (April 2015) - Borkett, Keith M.; Riff, Dennis S.; Schwartz, Howard I.; Winkle, Peter J.; Pambianco, Daniel J.; Lees, James P.; Wilhelm-Ogunbiyi, Karin
<x xml:space="preserve">Abstract</x> BACKGROUND: This exploratory study was the first study of remimazolam in patients to assess the safety and efficacy of different single doses for procedural sedation. METHODS: Patients scheduled to undergo a diagnostic upper gastrointestinal endoscopy were randomized to receive 1 of 3 doses of remimazolam or midazolam (25 per group) in a double-blind manner. After a single dose of study drug to achieve sedation, patients underwent gastroscopy. We assessed the success of the procedure, sedation levels, recovery from sedation, and safety. RESULTS: A single dose of remimazolam resulted in a successful procedure in 32%, 56%, and 64% of patients in the low (0.10), middle (0.15), and high (0.20 mg/kg) dose groups compared with 44% of patients in the midazolam (0.075 mg/kg) dose group. The onset of sedation was 1.5 to 2.5 minutes in the remimazolam dose groups compared with 5 minutes for midazolam. Because this was a single administration study, sedation could be maintained for as long as necessary to complete the procedure, using rescue midazolam or propofol. Recovery from sedation was rapid for all treatment groups but was influenced by the choice of rescue medication. There were no obvious differences in the safety profiles of remimazolam and midazolam. CONCLUSIONS: This exploratory dose-finding study showed that a single administration of remimazolam (0.10–0.20 mg/kg) was capable of inducing rapid sedation with a quick recovery profile in patients undergoing a diagnostic upper gastrointestinal endoscopy. The safety profile was favorable and appeared to be similar to that of midazolam, warranting further development of this short-acting compound.